FRI0335 Serum Levels of Immunoglobulins and Free Light Chains in Patients with Rheumatoid Arthritis Treated with Abatacept. (10th June 2014) - Scarsi, M.; Paolini, L.; Ricotta, D.; Colombo, E.; Pedrini, A.; Piantoni, S.; Caimi, L.; Tincani, A.; Airò, P.
Abstract : Background: Through costimulation blockade, Abatacept (ABA) may down-modulate the immune responses of B lymphocytes in Rheumatoid Arthritis (RA). We previously showed that ABA reduces the serum levels of different classes of anti-cyclic citrullinated peptide (anti-CCP), and rheumatoid factor (RF), and limits the differentiation of B lymphocytes into post-switch memory cells (1). Free light chains (FLC) are produced by B cells, plasmablasts and plasmacells and raised levels correlate with disease activity in RA. Objectives: To evaluate the effect of the ABA on serum levels of immunoglobulins (Ig) and FLC. To evaluate the baseline levels of these parameters as predictors of response to ABA. Methods: 30 RA patients (pts) (26 female; median-age: 53 years [IQR: 44-60] treated for at least 6 months with ABA and 24 healthy controls (HC; 18 female; age: 39 [34-46]) were evaluated. Serum Ig levels were measured by a nephelometric-immunoassay (Siemens Healthcare Diagnostics Products GmbH). Reference ranges were derived by a consensus group based on the standardization against the calibrated reference material CRM 470. Serum FLC levels were measured by a latex-enhanced immunoassay (The Binding Site, Birmingham, UK). Reference ranges include 100% of a population of 282 HC. Clinical disease activity was evaluated with the DAS28 (based on CRP). Results: At baseline (T0), RA pts had higher serum levels of IgM (p<0.05), IgA (p<0.001), free k chains (p<0.001), free λ chains (p<0.01), and k:λ ratio (p<0.01) than HC. In comparison with reference ranges, raised levels of serum IgG, IgA, IgM were observed in 17%, 37%, and 20% of RA pts, respectively; no one had hypogammaglobulinemia. Raised levels of k and λ FLC were demonstrated in 68% and 17% of pts. The k:λ ratio was above normal levels in 27% of them. After 6 months of ABA (T6), 53% of patients achieved the clinical remission; also a significant reduction of serum levels of IgG (p<0.001), IgA (p<0.001), and IgM (p<0.01) was seen. Baseline abnormal values of IgG, IgA, and IgM normalized at T6 in 2 of 5, 3 of 11 and 4 of 6 pts, respectively. Analogously, serum free k and λ chains decreased significantly at T6 (p<0.01 and p:0.01), normalizing respectively in 6 of 18, and 4 of 5 patients with raised levels at T0. The k:λ ratio was also significantly reduced after therapy (p:0.02), normalizing in 4 of 8 patients with raised ratio at T0. The decrease of FLC was significant only in patients with clinical remission at T6, but not in those without, whereas serum IgG and IgA levels decreased in both groups of patients. Moreover, the reduction of free λ chains was significantly correlated with the reduction of DAS28-CRP (r:0.47; p:0.01). Evaluating predicting biomarkers of response, baseline free λ chains serum levels were lower in patients achieving clinical remission at T6 than in the other pts (p:0.045). Conclusions: ABA therapy induced a trend toward normalization of serum levels of total Ig of different classes and of FLC. FLC reduction was significant in pts achieving clinical remission after ABA therapy, but not in those who did not. In our evaluation, the decrease of serum free λ chains was correlated with clinical improvement, and their baseline levels appeared to be associated with clinical response to ABA. References: Scarsi M et al; Ann Rheum Dis 2013;72(Suppl3):623 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5465